Implementation of E-Government Through E-Buddy in Sidoarjo Regency: Penerapan E-Government Melalui E-Buddy di Kabupaten Sidoarjo - Nadila, Difta Izza; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
This study examined the implementation of E-Buddy, an electronic official letter system, in a rural Indonesian village. Using observation, interviews, and document analysis, we found that while legal and technological frameworks were in place, human infrastructure posed significant challenges. Officials lacked training and understanding of E-Buddy, hindering its effectiveness. This highlights the crucial role of user-centric design and capacity building in successful e-government initiatives, particularly in resource-constrained settings. Highlight : The implementation of E-Buddy, an electronic official letter system, faced challenges due to inadequate communication and technical guidance The study revealed that the human resources, particularly the ability of village officials to adapt to the E-Buddy application, were not fully equipped for its implementation The research emphasizes the importance of user-centric design and capacity building in e-government initiatives, especially in resource-constrained settings Keywords: E-Government, E-Buddy, Implementation, Rural Village, Indonesia